2000
DOI: 10.1067/mtc.2000.110191
|View full text |Cite
|
Sign up to set email alerts
|

The atherosclerotic aorta at aortic valve replacement: Surgical strategies and results

Abstract: Aortic valve replacement in patients with severe atherosclerosis of the ascending aorta is associated with increased operative morbidity and mortality. Complete aortic valve replacement during hypothermic circulatory arrest, the "no-touch" technique, requires a prolonged period of circulatory arrest. Ascending aortic replacement is a preferred technique, as it requires a short period of hypothermic circulatory arrest and results in comparable mortality with a low risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 20 publications
1
80
0
Order By: Relevance
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if the aorta is not totally calcified and a noncalcified area is ascertained by epiaortic scanning and palpation, a "clampless" proximal anastomosis can be performed using a Heartstring device. 8,59,68 Lev-Ran et al 59 retrospectively compared the results of coronary revascularization between cardiopulmonary bypass with femoral artery cannulation in 15 patients and off-pump CABG in 41 patients with PA. There was only 1 case of perioperative mortality (2.4%) and there were no cases of perioperative stroke or transient ischemic attack in the off-pump CABG group.…”
Section: Pa and Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Although choosing a treatment strategy for patients with severe AS and a heavily calcified ascending aorta is not a new problem, the issues of surgical AVR in unclampable ascending aortas are worth revisiting because TAVI has been substantially developed as a treatment of choice for such patients. The average early mortality and stroke rate is 7-14% after surgical AVR in these patients according to previous reports (2,(4)(5)(6)(7)(8)(9). Therefore, opting for TAVI in these patients is a general trend in western countries.…”
Section: Discussionmentioning
confidence: 75%
“…The results of conventional surgical procedures on the atherosclerotic aorta during surgical AVR are well described in an article by Gillinov and colleagues (6). The sample size in their report was 62 patients.…”
Section: Variablesmentioning
confidence: 76%